Slope Adjustment of Runoff Curve Number (CN) using Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) Global Digital Elevation Model (GDEM) for Kuantan River Basin - Akbari, Abolghasem; Azizan, Abu Samah (2015)
The Natural Resources Conservation Service Curve Number (NRCS-CN) method is widely used for predicting direct runoff from rainfall. It employs the hydrologic soil groups and landuse information along with period soil moisture conditions to derive NRCS-CN. This method has been well documented and available in popular rainfallrunoff models such as HEC-HMS, SWAT, SWMM and many more. The SharplyWilliams and Hank methods was used to adjust CN values provided in standard table of TR-55. The Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) Global Digital Elevation Model (GDEM) is used to derive slope map with spatial resolution of 30 m for Kuantan River Bsin (KRB). The two investigated method stretches the conventional CN domain to the lower values. The study shows a successful application of remote sensing data and GIS tools in hydrological studies. The result of this work can be used for rainfall-runoff simulation and flood modeling in KRB.